Evaluation of Pediatric Patients with Orbital and Preseptal Cellulitis - (:unkn) unknown (CUKUROVA UNIV, FAC MEDICINE, 2015)
Purpose: Cellulitis in the orbital region is a relatively frequently observed ocular disease. Differential diagnosis of preseptal and orbital cellulitis is clinically possible. However physical examination may be insufficient for some differential diagnoses. The majority of pediatric patients with orbital and preseptal cellulitis present with complications of sinusitis. If left untreated it may cause vision loss and life-threatening intracranial complications. In this study we investigated the clinical findings, efficacy of treatment and complications of patients with orbital and preseptal cellulitis. Material and Methods: The files of all 28 in-patients with orbital and preseptal cellulitis who applied to our third stage pediatric clinic in the two years between January 2011 and January 2013 were retrospectively investigated. The demographic data, clinical presentation, predisposing factors, treatments and complications were analyzed. Results: Seven orbital cellulitis and 21 preseptal cellulitis patients fulfilling diagnostic criteria were included in the study. Twenty-five patients were treated with intravenous ampicillin-sulbactam and/or seftriakson. The most important predisposing factor in both patient groups was sinusitis while other predisposing factors were tooth abscess, conjunctivitis, chicken pox and leukemia. In five of every seven patients (71.4%) with orbital cellulitis, sinusitis is diagnosed. These five patients have ethmoidal sinusitis. Of every 21 patients with preseptal cellulitis, five (23.8%) have sinusitis. Of these five patients three have ethmoidal sinusitis. In the preseptal cellulitis group the median hospital stay was five days (3-21) while in the orbital cellulitis group the median stay was 21 days (8-35). In the preseptal cellulitis group while the median CRP was 15 mg/dL (1-141), median leukocyte count was 10600 u/L (800-23400) and median neutrophil count was 10100 u/L (200-21400), in the orbital cellulitis group the median CRP was 20 mg/dL (1-91), median leukocyte count was 14042 +/- 5498 u/L and median neutrophil count was 10571 +/- 2818 u/L. There was no statistically significant difference between the groups (p>0.05). The positivity in both swab cultures and blood cultures was at a very low level. All patients were discharged with full recovery. No patient required primary orbital surgical intervention. Conclusion: Preseptal cellulitis is more frequently observed than orbital cellulitis. The most important predisposing factor for orbital cellulitis is sinusitis. Patients with preseptal cellulitis suspected clinically may be diagnosed with orbital cellulitis radiologically. As a result radiological imaging of preseptal cellulitis patients should be considered.
Keywords: Orbital Cellulitis; Magnetic Resonance Imaging; Sinusitis; SINUSITIS; CHILDREN; COMPLICATIONS; MANAGEMENT